Co-management Options for Plantations Development : a Case Study from District Sirmour of Himachal Pradesh - Rana, P.; Singh, C. J. (Indian Forester, 2009)
Optimization of ecosystem goods and services from plantations depend on their sustainable production, protection and management. So far, the objective of attaining optimum production of environmental goods and services has remained a far cry due to uncontrolled exploitation, ignorance and inefficient management strategies. Informal understanding between the local field staff and communities for equitable distribution and utilization of plantations produce may act as an effective tool of sound management. Present paper points towards the efficiency of informal co-management strategies to improve, protect and utilize forest plantations and enhance the production of goods and services thereof. The study indicates how co-management strategies followed in Dharatidhar area of Paonta Sahib Forest Division of district Sirmour of Himachal Pradesh has not only led to the enhancement of goods and services from the unproductive areas but also developed a stake among the villagers to protect and enhance benefits from the plantations.